Warisan Budaya Nasional Pencak Silat dalam Mewujudkan Profil Pelajar Pancasila - Khairunnisa, Khairunnisa; Lisyawati, Elis; Halimah, Nur; Komara, Endang (EduInovasi: Journal of Basic Educational Studies, 2024)
Education and culture are closely integrated, because education is the process of transferring culture and reflecting cultural values. Pencak Silat is one of the national cultural heritages that can transform the values of Pencak Silat art through extracurricular education in realizing a sovereign, independent, and dignified Indonesia. Extracurricular Pencak Silat activities in the Merdeka Curriculum can contribute to the development of students' potential, interests, and talents. This study uses a qualitative approach that produces descriptive data through interviews, observations, and documentation of Pencak Silat extracurricular activities in 2023 at SMP Al-Aqsyar Parung Bogor, West Java. Based on the findings in the field, the Pencak Silat art provided by the school as an extracurricular activity can optimize the profile of Pancasila Students with a local wisdom theme. The implementation strategy to strengthen the profile of Pancasila Students is reinforced by Pencak Silat art through four aspects: spiritual, art, self-defense, and sports. These four aspects can strengthen the vision of the Ministry of Education and Culture 2020-2024, which is to realize a sovereign, independent, and dignified Indonesia through the creation of Pancasila Students who are critical, creative, independent, faithful, pious to Allah SWT, have noble character, collaborate, and embrace global diversity.